2003
DOI: 10.1016/s0167-2681(03)00030-1
|View full text |Cite
|
Sign up to set email alerts
|

The norm of restaurant tipping

Abstract: Using survey data, we identify a variety of factors that influence tipping behavior and in the process lay out a simple theoretical framework to help to interpret our empirical observations. We first investigate the efficiency of observed tipping behavior. While there are elements of efficiencynotably, percent tip depends on service quality-it does not appear fully efficient. We then posit a model in which customers trade off material well-being against disutility from not adhering to the norm, and we use this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
201
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(231 citation statements)
references
References 36 publications
(23 reference statements)
23
201
2
3
Order By: Relevance
“…Furthermore, frequent patrons tend to tip a higher percentage compared to infrequent patrons. Conlin et al (2003) also found a significant, positive correlation between tip size and patronage frequency.…”
Section: Patronage Frequencymentioning
confidence: 67%
See 3 more Smart Citations
“…Furthermore, frequent patrons tend to tip a higher percentage compared to infrequent patrons. Conlin et al (2003) also found a significant, positive correlation between tip size and patronage frequency.…”
Section: Patronage Frequencymentioning
confidence: 67%
“…Lynn and Grassman (1990) found no correlation between group size and tipping. However, Conlin et al (2003) found that tip percentage is positively correlated with group size.…”
Section: Dining Party Sizementioning
confidence: 92%
See 2 more Smart Citations
“…3 Frohlich et al (2004) and Conlin et al (2003) explore how contextual features of an environment influence norm-compliant behavior. However, they do not discuss this influence in the same way as when psychologists refer to focusing (or priming), and as we do here.…”
Section: Related Work On Norms and Focusingmentioning
confidence: 99%